The Kingdom of God in the Gospel of Matthew - Nohel, Petr (Civilia, 2019)
This article deals with Mathew's view of the phenomenon of God's Kingdom. Emphasis i sput on Chapter 13 due to the highest concentration of thematic parables. The topic of God's Kingdom, however, is not conceived a closed one. On the horizontal level it is set into the context of other Gospels. Vertically, the notion follows the significantly older tradition of Old Testament. The author also distinguishes different layers of meaning of the notion of God's Kingdom. Therefore, the interference with eschatology is present in this work.
Keywords: God's Kingdom; Parable; Bible; New Testament; Gospel of Matthew